2014
DOI: 10.1089/fpd.2013.1701
|View full text |Cite
|
Sign up to set email alerts
|

Development of asigDE-Based Real-Time Reverse-Transcriptase PCR for the Detection of ViableSalmonella enterica

Abstract: Salmonella is the most common cause of bacterial food poisoning in humans worldwide. Thus, rapid and reliable methods for the detection of this pathogen are required. Real-time reverse-transcriptase polymerase chain reaction (rt-RT-PCR), which detects the presence of mRNA (shorter half-life than DNA) has shown great potential for detecting viable pathogens. We recently identified a few new potential specific DNA sequences for Salmonella enterica using a comparative genomics method (Chen et al., 2010). In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Therefore, unlike DNA-based detection, mRNA would only be limited to the viable and active cells within the population. Based on this assumption, reverse-transcriptase quantitative PCR (RT-qPCR) assays have been developed to detect a variety of foodborne pathogens such as enterohemorrhagic E. coli , Listeria monocytogenes, Salmonella , Vibrio , and Campylobacter species ( Klein and Juneja, 1997 ; Sheridan et al, 1998 ; Szabo and Mackey, 1999 ; McIngvale et al, 2002 ; Yaron and Matthews, 2002 ; de Wet et al, 2008 ; D’Souza et al, 2009 ; Miller et al, 2010 ; Techathuvanan et al, 2010 ; Kurakawa et al, 2012 ; Zhou et al, 2014 ). However, while some reports have concluded that mRNA disappears quickly after cell death ( McIngvale et al, 2002 ), other findings suggest that transcripts can persist for extended lengths of time (e.g., Sung et al, 2005 ; Xiao et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, unlike DNA-based detection, mRNA would only be limited to the viable and active cells within the population. Based on this assumption, reverse-transcriptase quantitative PCR (RT-qPCR) assays have been developed to detect a variety of foodborne pathogens such as enterohemorrhagic E. coli , Listeria monocytogenes, Salmonella , Vibrio , and Campylobacter species ( Klein and Juneja, 1997 ; Sheridan et al, 1998 ; Szabo and Mackey, 1999 ; McIngvale et al, 2002 ; Yaron and Matthews, 2002 ; de Wet et al, 2008 ; D’Souza et al, 2009 ; Miller et al, 2010 ; Techathuvanan et al, 2010 ; Kurakawa et al, 2012 ; Zhou et al, 2014 ). However, while some reports have concluded that mRNA disappears quickly after cell death ( McIngvale et al, 2002 ), other findings suggest that transcripts can persist for extended lengths of time (e.g., Sung et al, 2005 ; Xiao et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although in several recent reports, some detection methods based on qPCR detected templates as low as 10–40 copy/μl or 10–100 CFU/ml (close to the sensitivity of the optimized bioluminescence pyrophosphate assay in this study), they all required quite expensive equipment and complex methods . However, in comparison, the assay proposed in this study costs less and is simpler and more convenient.…”
Section: Results and Disscussionmentioning
confidence: 48%
“…For example, Lee and others () measured S . Typhimurium and Salmonella Enteritidis in beef and pork at levels as low as 10 3 CFU/mL in as few as 6 h. One of the most promising PCR developments involves combination of qPCR with a reverse transcriptase technique (or RT‐qPCR), which has been used as a method for distinguishing between viable and nonviable cells (Zhou and others ). Remarkably, Zhou and others () detected viable Salmonella at a detection limit of 10 1 CFU/mL in egg broth and milk using the Salmonella ‐specific sigDE operon as a viability indicator, together with IMS and solvent extraction.…”
Section: Examples Of Devices For Pathogen Monitoringmentioning
confidence: 99%
“…Viability can be estimated by pretreating samples with reagents such as propidium monoazide (Li and others ) or monitoring the sigDE operon over time (Zhou and others ).…”
Section: Comparison Of Current and Emerging Techniques For Monitoringmentioning
confidence: 99%
See 1 more Smart Citation